Cognitive Function of the Elderly in Banjar Busana, Desa Sibanggede, Badung Regency: A Descriptive Study - Harry Bawana; Ni Nyoman Mestri Agustini; I Gede Surya Dinata; Ni Luh Kadek Alit Arsani (Warmadewa University, 2024)
Countries around the world are currently entering an aging population era, where the number of elderly individuals is increasing. In the elderly, there is a decline in intrinsic capacities such as physical, mental, and cognitive capacities, which hampers their functional abilities. Cognitive function impairment is an early stage of cognitive decline and is a risk factor for dementia, which significantly disrupts daily activities. Banjar Busana, Desa Sibanggede, is one of the banjars with a relatively large elderly population, totalling 117 individuals. However, data on the cognitive function profile in Banjar Busana, Desa Sibanggede, is not yet definitively available. This study aims to determine the cognitive function profile of the elderly in Banjar Busana, Desa Sibanggede, Badung Regency. The population of this study comprises all elderly individuals in Banjar Busana in 2023, totalling 117 people. The sample size was calculated using the formula by Dean et al., 2013, with a 95% confidence level, resulting in a sample size of 90 individuals. The sample was then selected using simple random sampling. Cognitive function was measured using the MoCA-INA questionnaire. The data were analyzed descriptively and quantitatively. The results showed that the majority of respondents were aged 60-69 years (59%), with more male respondents (51%) than female respondents (49%). Respondents experiencing cognitive function impairment amounted to 47%, while those without cognitive function impairment were 53%. It is recommended to provide more education to the community regarding the dangers of cognitive function impairment and preventive efforts.